2017
DOI: 10.1186/s12879-017-2862-2
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infections at a tertiary level paediatric hospital in South Africa

Abstract: BackgroundBloodstream infection (BSI) in children causes significant morbidity and mortality. There are few studies describing the epidemiology of BSI in South African children.MethodsA retrospective descriptive cohort study was conducted at a paediatric referral hospital in Cape Town, South Africa. The National Health Laboratory Service (NHLS) microbiology database was accessed to identify positive blood culture specimens during the period 2011–2012. Demographic and clinical details, antimicrobial management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
7
24
0
Order By: Relevance
“…[15] Research in Africa said that the most bacteria found in the study were Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia and Acinetobacter baumanii. [16] The bacteria found in this study were in line with the ve largest bacteria in our study, the 5 most germs only had a sequence different. Possibly caused by the two studies carried out in developing countries, with the type of bacteria that circulates similarly.…”
Section: Results This Research Was Conducted At H Adam Malik Generalsupporting
confidence: 83%
“…[15] Research in Africa said that the most bacteria found in the study were Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia and Acinetobacter baumanii. [16] The bacteria found in this study were in line with the ve largest bacteria in our study, the 5 most germs only had a sequence different. Possibly caused by the two studies carried out in developing countries, with the type of bacteria that circulates similarly.…”
Section: Results This Research Was Conducted At H Adam Malik Generalsupporting
confidence: 83%
“…Jimma 8.8% [8], Addis Ababa 32.8% [9] and other African countries like Tanzania 14.2% [10]; 24% [11], Gabon 17% [12], Burkina Faso 6% [13]in S. Africa 5.5% [14]; 5.7% [5]andamong Iranian neonates 6.4% [15]. Our results are comparable to study done inGondar, northern Ethiopia (39.5.9%) [16].…”
Section: Discussionsupporting
confidence: 82%
“…Regarding isolate, the current studyhas foundthat almost 43% of the isolates were CoNS and S. aureusfollowed byKlebsiella 21.4% which is similarwith other studies in Ethiopia, in Arsi [20] and Gondar [16] also with most of other studies in Africa.When we look report from African study, BSI study on neonatal in Tanzania reported that S. aureus 36.5% and Klebsiella 29.7% dominate all isolates recognized [21]there is also agreementwith report from S. Africa wereS. aureus, Klebsiella and E. coliare predominant isolate BSI among children [5]. Type of isolates in this study is still similar to that reported in other African studies for instant report from S. Africa shows predominate isolates S. aureus, Klebsiella [14]amongblood cultured samples of children.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Fifteen (16.5%) of the children had underlying chronic illnesses other than HIV infection, that was present for at least 6 weeks duration. Eleven children had malignancies, namely, acute lymphoblastic leukaemia (3), acute myeloid leukaemia (2), lymphoma (1), neuroblastoma (1), craniopharyngioma (1) and germ cell tumour (1). Other chronic diseases included chronic lung disease (2), Fanconi anaemia (1) and aplastic anaemia (1).…”
Section: Classi Cation and Risk Of Pseudomonas Aeruginosa Bsimentioning
confidence: 99%